2016
DOI: 10.1186/s40529-016-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

BnaABF2, a bZIP transcription factor from rapeseed (Brassica napus L.), enhances drought and salt tolerance in transgenic Arabidopsis

Abstract: BackgroundAbiotic stresses such as drought and salt stresses have a negative effect on the growth and productivity of plants. Improvement of stress tolerance through genetic engineering in plants has been reported in intense studies. Transcription factors play vital roles in plant adaptation to stresses by regulating expression of a great deal of target genes. A family of Arabidopsis basic region leucine zipper (bZIP) transcription factors that can recognize and bind to the abscisic acid (ABA)-responsive eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…The five TF families play important roles during stress response in plants [ 30 , 32 , 35 , 40 ]. For B. napus , we consider five treatments, including cold, heat, drought, salt and ABA ( Material and methods ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The five TF families play important roles during stress response in plants [ 30 , 32 , 35 , 40 ]. For B. napus , we consider five treatments, including cold, heat, drought, salt and ABA ( Material and methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Hwang et al identified 136 BrbZIPs [ 31 ] in B. rapa and 119 BobZIPs [ 24 ] in B. oleracea , and cold responsiveness of these TFs were investigated by using RNA-Seq and qRT-PCR. Zhao et al [ 32 ] found that the expression of a bZIP gene, BnABF2 in B. napus , could be induced by drought and salt stresses. Zhou et al [ 8 ] identified 247 BnbZIPs in B. napus and performed detailed structural analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these synthetic promoters contained DREs and ABREs. DREB2A (dehydration-responsive element binding protein 2A) regulates DRE-mediated element of genes under osmotic stress conditions in Arabidopsis [ 41 , 42 ], and ABRE binding factors (ABFs)/ABRE binding proteins (AREBs) are highly induced by ABA and then interact with ABREs to cause gene expression [ 43 ]. To further determine whether the synthetic promoters were induced by DREB2A or ABA, the ratio of FLUC (Firefly luciferase)/RLUC (Renilla luciferase) was analyzed in Arabidopsis protoplasts by the dual-luciferase reporter system.…”
Section: Resultsmentioning
confidence: 99%
“…In B. napus 247 bZIP TFs have been identified, and their differential expression in various tissues and organs has been reported (Zhou et al, 2017). Zhao B. Y., et al (2016) reported the expression of BnABF2 (gene encoding bZIP factor) in response to drought and salt stress. Further, overexpression of BnABF2 in Arabidopsis conferred drought and salt resistance due to regulation of RD29B, RAB18, and KIN2 genes under these stresses in an ABA-dependent manner.…”
Section: Nacs Tfsmentioning
confidence: 99%